2021
DOI: 10.3390/su13115965
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility, Sustainability, Sustainable Development and Corporate Sustainability: What Is the Difference, and Does It Matter?

Abstract: The terms “corporate social responsibility” (CSR), “sustainability”, “sustainable development” and “corporate sustainability” (CS) are critical terms for developing, analysing and evaluating public and private policy goals. These terms are used to make decisions about investment, policy development, and strategy creation. The terms emerged in different fields of endeavour at different points in time. Accordingly, they have different meanings; however, over time they have come to be used interchangeably mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 60 publications
3
61
0
4
Order By: Relevance
“…Hundreds of works have been devoted to corporate social responsibility, from which two most cited (according to "Scopus" on 19 June 2021) are the seminal articles by Orlitzky et al (2003) and Porter and Kramer (2006), which not only provide a theoretical framework but also argue for benefits of social responsibility to companies and their competitive advantages and performance. Nonetheless, many related issues (these are almost philosophical sometimes) remain debatable, as one can find in two very fresh examples (Fraser et al 2021;Sheehy and Farneti 2021). The meaning of patriotism (Clift and Woll 2012;Schatz et al 1999;Turner 2002; see also remarks given in the introductory part of this work) allows one to connect this phenomenon to corporate social responsibility.…”
Section: Brief Literature Reviewmentioning
confidence: 95%
“…Hundreds of works have been devoted to corporate social responsibility, from which two most cited (according to "Scopus" on 19 June 2021) are the seminal articles by Orlitzky et al (2003) and Porter and Kramer (2006), which not only provide a theoretical framework but also argue for benefits of social responsibility to companies and their competitive advantages and performance. Nonetheless, many related issues (these are almost philosophical sometimes) remain debatable, as one can find in two very fresh examples (Fraser et al 2021;Sheehy and Farneti 2021). The meaning of patriotism (Clift and Woll 2012;Schatz et al 1999;Turner 2002; see also remarks given in the introductory part of this work) allows one to connect this phenomenon to corporate social responsibility.…”
Section: Brief Literature Reviewmentioning
confidence: 95%
“…There are many interpretations for the definition of sustainability, from environmental ecology, economic development, and social tolerance to licensing and other perspectives [42]. Recent studies have shown that organizational sustainability has surpassed the traditional concept "green" and no longer stays at the behavior of, for example, reducing negative environmental impacts, but moves into a more comprehensive and systematic understanding [43,44].…”
Section: Methods Describing and Systematizing The Literaturementioning
confidence: 99%
“…The term "sustainable development" has a strong focus on social-economic development and the opening of new markets [59]. In order to achieve the goal of sustainable development for enterprises and parks, park managers need to take measures to promote the sustainable emergence of enterprise cooperation in the network.…”
Section: Management Implicationsmentioning
confidence: 99%